Musikkfilosofiske tekster Tanker om musikk - og språk, tolkning, erfaring, tid, klang, stillhet m.m. - Varkøy, Øivind; Holm, Henrik (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"To pursue the philosophy of music is to contemplate music's nature, essence, purpose, value, and function in our lives. While the aesthetics of music looks at music's content, quality, meaning and importance, music philosophy often goes one step further. Ideas about something one perhaps believes is 'purely aesthetical' will of course always require consideration in relation to ideas about humanity, the world, politics and religion. In this sense, music aesthetics and music philosophy are two sides of the same coin. This is reflected in the texts presented in this collection, which provides a broad view of the current state of ideas about music in Norway. The authors, from PhD fellows to emeriti, represent different higher educational music institutions in Norway as well as different fields within music and philosophy. Their texts are on topics ranging from musical experience, music and language, meaning and interpretation of music, music and view of life, and others. The anthology's editors Øivind Varkøy and Henrik Holm are, respectively, professor of music education and director of the PhD program at the Norwegian Academy of Music and adjunct professor of music at Oslo Metropolitan University, and professor of philosophy and head of research at Rudolf Steiner University College in Oslo."